Rhetoric and Logical Reasoning as Engagement with Being - Barris, Jeremy (Informal Logic, 2019)
The paper tries to show that when the deepest or foundational aspects of truth are at issue, both consequentially logical argument and rhetoric that aims to establish truth or justified conviction must engage with the being, or the irreplaceable particularity, of its audience’s members and also that of the arguer, what we refer to in ordinary language as who the person is. Beyond the existing discussion of existential rhetoric, the paper argues that this engagement with being is necessary to establish not only truth that directly concerns or turns on the arguer’s and audience’s being, but also truth or justification about fundamental aspects of things and issues in general. Further, the address of being requires us to suspend both our own and our addressees’ familiar conceptual frameworks in order to allow being to emerge in its own terms. As a result, in contrast with our usual understanding of argumentation, the rhetorician’s initial aim and procedure will be to achieve a genuine suspension of conviction and even of the appropriate concepts under which to proceed, and so to produce a fundamental confusion. The paper then outlines some consequences for rhetoric and reasoning and also the structure of the process of working with this fundamental confusion.